Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1752-1947-6-59
|View full text |Cite
|
Sign up to set email alerts
|

Mycotic pseudoaneurysms complicating renal transplantation: a case series and review of literature

Abstract: IntroductionKidney transplantation can be complicated by infection and subsequent development of mycotic aneurysm, endangering the survival of the graft and the patient. Management of this condition in five cases is discussed, accompanied by a review of the relevant literature.Case presentationsFive patients, three men 42-, 67- and 57-years-old and two women 55- and 21-years-old (mean age of 48 years), all Caucasians, developed a mycotic aneurysm in the region of the anastomosis between renal graft artery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 12 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…Surgical management planning should include the monitoring of any distant septic source [1,12]. A treatment modality is the excision of the infectious aneurysm and placement of prosthetic material preferably medicated; another modality is the endovascular management [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical management planning should include the monitoring of any distant septic source [1,12]. A treatment modality is the excision of the infectious aneurysm and placement of prosthetic material preferably medicated; another modality is the endovascular management [12].…”
Section: Discussionmentioning
confidence: 99%
“…Leonardou, et al reported a 5 case series of mycotic aneurysm in kidney transplant recipients, using a combination of antibiotic therapy, surgery and interventional procedures, with a 100% survival of the patient, but graft lost in all cases [12].…”
Section: Discussionmentioning
confidence: 99%
“…While anastomotic pseudoaneurysms have been reported since 1985, 2 infectious pseudoaneurysms have been rarely reported and were often associated with graft loss in the case reports and series available in literature (Table 1). 3,4 They usually present with a wide spectrum of presentation, ranging from iliac fossa pain and fever to lower limb ischemia or even hemorrhagic shock due to rupture of pseudoaneurysm. Causes of infectious aneurysm formation are multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Leonardou et al reported two cases with P. aeruginosa isolated from the blood culture, and both patients were treated with ciprofloxacin for 4 weeks in total after surgery. 4 No recurrence was detected up to 36 months. Unfortunately, in our patient, no single antibiotic agent was able to control the infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation